Regulation of mammalian spliceosome assembly by a protein phosphorylation mechanism. - Mermoud, J E (1994)
Splicing of mRNA precursors (pre-mRNA) is preceded by assembly of the pre-mRNA with small nuclear ribonucleoprotein particles (snRNPs) and protein factors to form a splicesome. Here we show that stimulating Ser/Thr-specific protein dephosphorylation selectively inhibits an early step during mammalian spliceosome assembly. Treatment of HeLa nuclear splicing extracts with human protein phosphatase 1 (PP1) expressed in Escherichia coli, or PP1 purified from rabbit skeletal muscle, prevents pre-spliceosome E complex (early complex) formation and stable binding of U2 and U4/U6.U5 snRNPs to the pre-mRNA. PP1 does not inhibit splicing catalysis if added after spliceosome assembly has taken place. Addition of purified SR protein splicing factors restores spliceosome formation and splicing to PP1-inhibited extracts, consistent with SR proteins being targets regulated by phosphorylation. These data extend earlier observations showing that splicing catalysis, but not spliceosome assembly, is blocked by inhibiting protein phosphatases. It therefore appears that pre-mRNA splicing, in common with other biological processes, can be regulated both positively and negatively by reversible protein phosphorylation.